Review of the main traditional cheese-making in the Mediterranean basin - Férial Aziza Benyahia; Adel Bouali; Batoul Meghzili; Esma Foufou; Sami Saadi; Lamia El-Mechta; Ouarda Aissaoui Zitoun (Journal of Ethnic Foods)
Abstract The article delves into the rich history of dairy products, tracing their evolution from simple milk to a diverse array of derivatives, with specific focus on traditional cheese varieties originating from the Mediterranean region. It underscores the nutritional importance of dairy, emphasizing its abundance in vital nutrients such as proteins, lipids, and minerals. Our particular interest is the intricate process by which milk is transformed into cheese, a method that effectively preserves nutrients over extended periods. Enzymes play a key role in enhancing food quality throughout the production process. Despite the commercialization of certain cheese varieties, many remain unbranded, crafted for local consumption or distributed in an artisanal fashion. Nonetheless, the traditional quality associated with farm-based production is gradually waning in rural landscapes. The primary objective of the study is to meticulously identify and safeguard the legacy of traditional Mediterranean cheese varieties, recognizing their profound cultural and gastronomic significance. This research aims to preserve their vitality and support the conservation of an ancestral culinary heritage at risk of disappearing.